Rancang bangun prototype tungku induksi untuk proses perlakuan panas - Muchamad Fajrin Darmawan; Sulaeman Deni Ramdani; Moch Fawaid (Jurnal Taman Vokasi, 2020)
This research aims for 1). Performance of induction furnace used to heat test objects in the form of iron, stainless steel and aluminum 2). Efficiency of induction furnace in heating test objects in the form of iron, staineless and aluminum. The research method used in this study is purely experimental where data is obtained from the heating of test objects in the form of iron, aluminum and stainless steel. 1). At the time of the induction furnace performance test was conducted 13 experiments, out of 13 tests got the highest temperature of 650o C on the thirteenth experiment and failed on the second, fifth and ninth trials where MOSFET was damaged. 2). Induction furnace in heating iron weighing 5 grams produces a calorific 1302.57 joules and produces 49.16 Watts of power. Induction furnace in heating aluminum weighing 5 grams produces a 5.22 joule calorific and produces 0.029 Watts of power. Induction furnace in heating stainless steel weighing 5 grams produces a calorific 1440.52 joules and produces 42.66 Watts of power. so the induction furnace is more efficient when it is heating test objects in the form of iron and the induction furnace cannot heat test objects that do not have magnetic properties.